Efficiency and effectiveness of marketing of the hotels in Kuala Lumpur - Rahmati, Elham; Abdul Jalil, Suhaila (Faculty of Economics and Management, Universiti Putra Malaysia, 2014)
This study employs a separate two-stage DEA model to measure marketing efficiency and marketing effectiveness of three- to fivestar hotels in Kuala Lumpur for the period between 2004 and 2010. The results indicate those hotels with lower number of stars face less technical problems in transforming the marketing inputs to the utilized service capacity, namely the occupied rooms. However, the hotels, particularly the lower star-ranking ones have considerable managerial problems in transforming the utilized service capacity into profit. Finally based on the slack analysis, the necessary improvements of the marketing factors and profit are presented in order to catch up with the efficient frontier.